Impact of neck failure on survival in older patients with differentiated thyroid cancer. Issue 6 (13th February 2016) - Marcus, David M.; Jiang, Renjian; Ward, Kevin C.; Higgins, Kristin A.; Saba, Nabil F.; Wadsworth, J. Trad; Beitler, Jonathan J.
Abstract: Background: Regional recurrence of differentiated thyroid cancer (DTC) is often salvaged with neck dissection without survival penalty. It is unknown whether recurrence may be associated with inferior survival in older patients. Methods: Surveillance, Epidemiology, and End Results (SEER) and Medicare data were linked to identify patients age ≥65 with nonmetastatic DTC. Patients undergoing neck dissection >6 months after their initial diagnosis were considered to have regional recurrent disease. We compared overall survival (OS) and cause‐specific survival (CSS) for patients with recurrent disease versus a matched cohort of patients with non‐recurrent DTC. Results: Of 6235 patients, 143 had treatment‐defined recurrent disease. Patients with recurrent disease had inferior OS ( p < .01) and CSS ( p < .01). Multivariate analysis demonstrated that recurrent disease was independently associated with inferior 10‐year OS (hazard ratio [HR] = 1.75; p < .01) and CSS (HR = 3.05; p < .01). Conclusion: Regional recurrence of DTC may negatively impact OS and CSS in patients ≥65 years old. © 2016 Wiley Periodicals, Inc. Head Neck 38: 919–924, 2016